wp 2011
DOI: 10.24149/wp1110
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy and Mortgage Equity Withdrawals

Abstract: The recent U.S. consumption boom and the subsequent surge in mortgage defaults have been linked to mortgage equity withdrawals (MEWs). MEWs are correlated with covariates consistent with a permanent income framework augmented for credit-constraints. Nevertheless, many households are financially illiterate. We assess the unexplored linkages between "active MEW" and measures of financial literacy using panel data from the Health and Retirement Study (HRS). Findings indicate that declines in mortgage interest rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…The usage of simple questions pertaining key parameters of debt-such as interest and commission-can also be justified by findings of foreign researchers. For instance, Bucks and Pence (2008) as well as Duca and Kumar (2014) found that many borrowers have serious problems with understanding and providing information on basic characteristics of their loans, such as the interest rate.…”
Section: Methodsmentioning
confidence: 99%
“…The usage of simple questions pertaining key parameters of debt-such as interest and commission-can also be justified by findings of foreign researchers. For instance, Bucks and Pence (2008) as well as Duca and Kumar (2014) found that many borrowers have serious problems with understanding and providing information on basic characteristics of their loans, such as the interest rate.…”
Section: Methodsmentioning
confidence: 99%
“…Schicks (2014) analyzes the overindebtedness of micro borrowers in Ghana and maintain that overindebtedness is lower for borrowers with a good debt literacy. Another case is found with mortgage equity withdrawals 6 (Duca and Kumar, 2014); people with a higher financial literacy are less likely to withdraw housing equity. Agarwal et al (2015c) use a dataset from one of the leading subprime lenders in the United States and find that borrowers from the financial industry, who have a higher financial literacy, are less likely to default.…”
Section: Introductionmentioning
confidence: 93%
“…Reed (2009) finds that, among Australian homeowners who claimed to be aware of RMs, only 40% understood the basic features, specifically, that no repayments were due and that the house would not be sold. Duca and Kumar (2010) also report a positive correlation between households with mortgage equity withdrawals and lack of financial literacy.…”
Section: Rms: An Overviewmentioning
confidence: 99%